2019
DOI: 10.3389/fspor.2019.00002
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Protective Headgear in Attenuating Ball-to-Forehead Impacts in Water Polo

Abstract: Recent reports have demonstrated that there is a serious risk of head impact and injury in water polo. The use of protective headgear in contact sports is a commonly accepted strategy for reducing the risk of head injury, but there are few available protective headgears for use in water polo. Many of those that are available are banned by the sport's governing bodies due to a lack of published data supporting the effectiveness of those headgears in reducing head impact kinematics. To address this gap in knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…20,21 Although none of the athletes we monitored wore protective headgears, the characterization of head impacts in the present study can inform the design of protective water polo headgears and the methods used to test their efficacy. A previous study of protective water polo headgears reported attenuated head impact magnitudes from a ball launched at the front of the head, 22 an impact scenario commonly self-reported in an epidemiological survey of water polo players. 15 However, ball impacts and front impacts were relatively uncommon in this cohort.…”
Section: Discussionmentioning
confidence: 87%
“…20,21 Although none of the athletes we monitored wore protective headgears, the characterization of head impacts in the present study can inform the design of protective water polo headgears and the methods used to test their efficacy. A previous study of protective water polo headgears reported attenuated head impact magnitudes from a ball launched at the front of the head, 22 an impact scenario commonly self-reported in an epidemiological survey of water polo players. 15 However, ball impacts and front impacts were relatively uncommon in this cohort.…”
Section: Discussionmentioning
confidence: 87%
“…V súčasnosti existuje mnoho spôsobov, ako chrániť ušnicu pred vonkajšími vplyvmi, či už mechanických alebo akustickými. Zároveň bolo vytvorených mnoho štúdií, ktoré sa venujú hodnotením efektivity chráničov uší [7][8][9][10][11][12][13]. Výskum je zameraný na návrh personalizovaného chrániča uší, ktorého použitie je vhodné ako pre profesionálnych športovcov, tak aj pre ľudí, ktorým hrozí riziko fyzického poranenia uší pri vykonávaní ich práce, športu, či voľnočasových aktivít.…”
Section: úVodunclassified